Enhanced efficiency of photovoltaic thermal systems using graphene nanoplatelets nanofluid - Mohd Rosli, Mohd Afzanizam; Muhamed Rafaizul, Nurul Izzati Akmal; Puspitasari, Poppy; Permanasari, Avita Ayu; Abdullah, Norli; Gazali Herawan, Safarudin; Abdul Rashid, Azrin Hani; Hussain, Faridah (Penerbit Akademia Baru, 2025)
Photovoltaic thermal (PV/T) systems have become a promising technology for using solar radiation to generate thermal and electrical energy. However, the overheating tendency of PV cells can reduce the electrical output of PV/T systems, thereby limiting their efficiency. One way to increase the efficiency of PV/T systems is the utilization of nanofluids as the working fluid. This investigation uses water-based nanofluids based on graphene nanoplatelets to study the efficiency of PV/T systems. Graphene nanoplatelets (GNP), the nanofluids, were prepared at a mass fraction of 0.6 wt.%, which, due to its thermophysical characteristics, was determined to be the ideal weight percentage. The surfactant utilized in this study was polyvinylpyrrolidone (PVP) to improve the stability of the nanofluid and an amount of 40% from the GNP weight percentage was used as the weight percentage of the surfactant. The two-step method is implemented to formulate the nanofluid. The results obtained shows that the GNP/water nanofluids provide better thermal and electrical efficiency compared to distilled water with the highest thermal and electrical efficiency obtained was 80% and 8.9%, compared to water, 66.5% and 8.8%, respectively, and the overall enhancement of 17% at different flow rates and solar irradiance levels, emphasizing the significant role of nanofluid technology in advancing the sustainability and effectiveness of solar energy applications. This proved that the nanofluid could boost energy conversion and system efficiency because of its increased thermal and electrical efficiencies.